Validity And Practicality of PjBL-Based Teaching Materials Environmental Pollution For Physics Phase E - Rahmadini, Fadhilla; Darvina, Yenni; Gusnedi, Gusnedi; Yulia Sari, Silvi (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2024)
The purpose of this research is to test the validity and practicality of the project-based learning teaching materials that have been developed.. This research is research and development (R&D) with a model-4D development model. Data analysis uses Aiken V. The results of the validity test, gets a score was 0.89846 with valid criteria. Meanwhile, the results of the practicality test by 3 physics teachers obtained an average overall score of 93.25% using practical criteria, and the results of the practicality test by 19 students obtained an average overall score of 88.28% using practical criteria, so it can be concluded that the environmental pollution teaching materials for phase E project-based learning that have been developed have met the validity and practicality requirements and are suitable for use by teachers in teaching and for students in learning.